‘“Health” Is Just One Piece in the Puzzle of Wellbeing’: Shifting From Preventing Health Deterioration to Improving Wellbeing in a Participatory Action Research Project With Care‐Experienced Older People - Sarah Wallcook; Ulla Dahlkvist; Yvonne Domeij; Kerstin Green; Gigi Isaksson; Ida Goliath (Health Expectations)
ABSTRACT Introduction Prevention of health deterioration is a key policy objective in Sweden informed by active and healthy ageing initiatives. However, the perspectives of older people with mobility and health limitations on current prevention initiatives are seldom gained meaning these initiatives may fail to align to with the priorities of people whose health has ostensibly already deteriorated. We aimed to explore older care‐experienced people's perspectives on the topic of health deterioration prevention and highlight aspects that they think are important to prioritise. Method Eight older people with experience in giving or receiving formal or informal care were involved as lay co‐researchers in a participatory action research project that involved recruiting 11 further older informants to participate in peer interviews or complete a logbook. In a series of 13, 2‐h workshops held over 1 year, we undertook data generation, training, reflection and analytic activities inspired by framework analysis. Findings The lay co‐researchers found the topic of health deterioration to be negatively and narrowly focussed opting instead to pursue a focus on articulating aspects, or puzzle pieces, that influence the improvement of wellbeing. Six influential puzzle pieces (stigma, digitalisation, services, losses, meaning and interactions) were regarded as important to prioritise which together illustrated that wellbeing is continually shaped in an interplay with dominant, but manipulable, social norms. Conclusion This study highlights how the language of active and healthy ageing, which pervades policy and practice, is imbued with ageist and ableist subtexts that can influence older people's wellbeing and lead to exclusionary experiences in society. We highlight wider societal trends, particularly digitalisation and effectivisation, whose negative impact on older people's wellbeing could be mitigated through inclusive co‐design and resistance to normative influences. Public Contribution This project was initiated in dialogue with stakeholder representatives from pensioner organisations in a larger scale participatory action research project. The care‐experienced lay co‐researchers collaborated in all phases of this project—gaining funding, formulating research questions, planning the study design, generating data in peer interviews, analysing and interpreting data, disseminating findings, prioritising future research and co‐authoring articles.